Atypical progression of delayed encephalopathy post-carbon monoxide poisoning with fluctuating psychotic symptoms: a case report - Yunhan Lin; Yunhan Lin; Yan Shao; Yan Shao; Xinyu Sun; Xinyu Sun (Frontiers in Psychiatry, 2025)
ObjectivesThis report details a case of delayed encephalopathy after acute carbon monoxide poisoning (DEACMP), a condition with significant neuropsychiatric sequelae that is often underrecognized. The case is notable for its atypical progression and poor response to conventional treatments, highlighting the need for awareness and novel approaches in managing similar cases.Case reportMrs. C, a 53-year-old female with a long history of recurrent depression, suffered from severe carbon monoxide poisoning. Despite initial recovery, she exhibited a relapse marked by profound cognitive decline and erratic behaviors such as inappropriate urination and fecal smearing. The diagnostic workup, including MRI and neuropsychological testing, confirmed DEACMP. Various treatments were employed with limited success. Her course of illness underscores the fluctuating nature of her symptoms and the overall decline in her cognitive function.ConclusionsThis case underscores the complex clinical management and refractory nature of DEACMP, emphasizing the necessity for comprehensive, individualized treatment approaches. The insights provided here advocate for heightened surveillance during the ‘false recovery period’ and tailored therapeutic strategies to alleviate symptoms, improve quality of life, and minimize long-term neurological damage in patients suffering from DEACMP.